Lox-dependent gene expression in transgenic plants obtained via Agrobacterium-mediated transformation - Shcherbak, N.; Kishchenko, O.; Sakhno, L.; Komarnytsky, I.; Kuchuk, M. (Цитология и генетика, 2013)
Lox sites of the Cre/lox recombination system from bacteriophage P1 were analyzed for their ability to affect on transgene expression when inserted upstream from a gene coding sequence adjacent to the right border (RB) of T-DNA. Wild and mutated types of lox sites were tested for their effect upon bar gene expression in plants obtained via Agrobacterium-mediated and biolistic transformation methods. Lox-mediated expression of bar gene, recognized by resistance of transgenic plants to PPT, occurred only in plants obtained via Agrobacterium-mediated transformation. RT-PCR analysis confirms that PPT-resistant phenotype of transgenic plants obtained via Agrobacterium-mediated transformation was caused by activation of bar gene. The plasmid with promoterless gus gene together with the lox site adjacent to the RB was constructed and transferred to Nicotiana tabacum as well. Transgenic plants exhibited GUS activity and expression of gus gene was detected in plant leaves. Expression of bar gene from the vectors containing lox site near RB allowed recovery of numerous PPT-resistant transformants of such important crops as Beta vulgaris, Brassica napus, Lactuca sativa and Solanum tuberosum. Our results demonstrate that the lox site sequence adjacent to the RB can be used to control bar gene expression in transgenic plants.